Effects of haloperidol and clozapine on synapse-related gene expression in specific brain regions of male rats - Wilmsdorff, Martina Klara Pauline von; Gebicke-Härter, Peter J. (European archives of psychiatry and clinical neuroscience, 2018)
We investigated the effects of clozapine and haloperidol, drugs that are widely used in the treatment of schizophrenia, on gene expression in six cortical and subcortical brain regions of adult rats. Drug treatments started at postnatal day 85 and continued over a 12-week period. Ten animals received haloperidol (1 mg/kg bodyweight) and ten received clozapine (20 mg/kg bodyweight) orally each day. Ten control rats received no drugs. The ten genes selected for this study did not belong to the dopaminergic or serotoninergic systems, which are typically targeted by the two substances, but coded for proteins of the cytoskeleton and proteins belonging to the synaptic transmitter release machinery. Quantitative real-time PCR was performed in the prelimbic cortex, cingulate gyrus (CG1) and caudate putamen and in the hippocampal cornu ammonis 1 (CA1), cornu ammonis 3 (CA3) and dentate gyrus. Results show distinct patterns of gene expression under the influence of the two drugs, but also distinct gene regulations dependent on the brain regions. Haloperidol-medicated animals showed statistically significant downregulation of SNAP-25 in CA3 (p = 0.0134) and upregulation of STX1A in CA1 (p = 0.0133) compared to controls. Clozapine-treated animals showed significant downregulation of SNAP-25 in CG1 (p = 0.0013). Our results clearly reveal that the drugs' effects are different between brain regions. These effects are possibly indirectly mediated through feedback mechanisms by proteins targeted by the drugs, but direct effects of haloperidol or clozapine on mechanisms of gene expression cannot be excluded.
Gesehen am 09.04.2019